2016
DOI: 10.1590/01047760201622032169
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Water in Living Woody Stems - A Review

Abstract: Predicted climate changes due to greenhouse gas emissions will alter site and ecological conditions, increase instability in many ecosystems and expand the value of forest carbon and wood energy. Woody plants most often are faced with drought stresses, not only because of erratic rainfall, but also the result of climatic changes. Natural variability among wood species in terms of chances in induced water stress in stem moisture content is large. Under severe water deficit, plants have to face the dilemma of dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
0
6
0
1
Order By: Relevance
“…So even though one could argue that current NDVI‐derived VWC estimates are sufficiently differentiated for global model purposes, when applied in the perspective of climate change impacts, the estimation of effects of drought stress to vegetation becomes essential. The improved understanding of responses of plants to drought stress ruled by water potentials in soils stems, strongly depending on soil type/properties (Malavasi et al, ), offers crucial information to feed such models, possible through improved parameterization of VWC with PTFs.…”
Section: Challenges For Ptfs In Earth System Sciencementioning
confidence: 99%
“…So even though one could argue that current NDVI‐derived VWC estimates are sufficiently differentiated for global model purposes, when applied in the perspective of climate change impacts, the estimation of effects of drought stress to vegetation becomes essential. The improved understanding of responses of plants to drought stress ruled by water potentials in soils stems, strongly depending on soil type/properties (Malavasi et al, ), offers crucial information to feed such models, possible through improved parameterization of VWC with PTFs.…”
Section: Challenges For Ptfs In Earth System Sciencementioning
confidence: 99%
“…Gibbs (1930) demonstrated a seasonal variation in tree stem water content (θstem = volume of water/total volume of stem), also referred to as stem relative water content (Malavasi et al, 2016). θstem varied with xylem water potential, and different environmental factors including soil water status, climatic conditions or present tree disease.…”
Section: Tree Trunk Water Contentmentioning
confidence: 99%
“…Methods, including the dendrometer (Turcotte et al, 2011), coring and gravimetric analysis (Clark and Gibbs, 1957;Waring and Running, 1978;Waring et al, 1979), gamma-ray attenuation (Brough et al, 1986;Edwards and Jarvis, 1983), MRI-nuclear magnetic resonance imaging (Choat et al, 2010;De Schepper et al, 2012;Reinders et al, 1988a;Reinders et al, 1988b;Windt et al, 2009), X-ray computer tomography (Raschi et al, 1995), stem diameter transduction (Cuevas Sánchez and Fernández Luque, 2010), ultrasonic echo detection (Lyu et al, 2016), TDR (Dahlen et al, 2015;Hernández-Santana and Martínez-Fernández, 2010;Irvine and Grace, 1997;Nadler et al, 2003;Wullschleger et al, 1996), FDR-frequency domain reflectometry (Beedlow et al, 2017;Kumagai et al, 2009;Zhou et al, 2018), and heat tracer methods (Trcala et al, 2015), were demonstrated to determine stem water content/storage. More details about the pros and cons of the approaches to the measurement can be found in Malavasi et al (2016).…”
Section: Tree Trunk Water Contentmentioning
confidence: 99%
See 2 more Smart Citations